Dos supervivientes visigóticos (Zamora, AHP, fragmentos 15 y 202) - Suárez González, Ana (Miscel·lània litúrgica catalana, 2006)
The fragments nos. 15 and 202 of the Provincial Historical Archive of Zamora convey the new Roman rite still in a graphic presentation rather close to old Hispanic liturgy. Both folios, of North-western origin, date from between the end of the 11th and the beginning of the 12th century. Both bear a decadent Visogothic writing and refer to different books: a misticus (fragment no. 15) and a missal (fragment no. 202). The study analyses externally and internally both pieces on parchment and their text is also edited as a small contribution to history of liturgy.